Technological innovation and cleaner energy consumption impact on economic growth and employment in the MENA region - Salwa Bajja; Gabriel Mordzifa Sackitey; Michael Provide Fumey (Environmental and Sustainability Indicators)
This study investigates the impact of technological innovation and cleaner energy consumption on economic growth and employment in the MENA region using panel data from seven countries from 1990 to 2022. Employing the Driscoll-Kraay Standard Errors (DKSE) model, we estimate the effects of key determinants, including technological innovation, manufacturing value-added, urbanization, renewable energy consumption, total energy consumption, and financial development, on economic performance and labor market dynamics. Our findings reveal that technological innovation and urbanization contribute to economic growth while fostering employment opportunities. Additionally, manufacturing value-added and financial development emerge as crucial drivers of economic expansion, whereas urbanization and total energy consumption exhibit mixed effects. These results underscore the importance of policy measures promoting technological advancements and sustainable energy use to enhance economic resilience and job creation in the MENA region.